An In Situ Study of the Topochemical Transformation of Hybrid Layered Hydroxides Into Metallic Nanocomposites - Jaramillo Hernández, Camilo (2025)
The urgent transition toward sustainable energy systems requires the development of advanced nanomaterials. Among them, nanocomposites composed of inorganic nanoparticles embedded in a graphitic matrix offer exceptional redox properties, electrical conductivity, and mechanical stability, making them highly attractive for electrochemical applications. While typically synthesized via high-temperature calcination of Metal-Organic Frameworks, Layered Hydroxides (LHs) represent a promising alternative due to their anisotropic nature, chemical versatility, and scalable, well-established synthesis routes. However, the mechanism behind their transformation into nanocomposites remains poorly unexplored. Herein, in situ synchrotron-based techniques are employed to investigate the topochemical transformation of 2D cobalt-based LHs into nanocomposites thanks to the templating and reducing effect exerted by intercalated carboxylic molecules. Experiments reveal that the length of dicarboxylic anions governs the transformation mechanism, balancing the inherent anisotropy and reactivity: short chains hinder nanocomposite formation, whereas longer chains promote it. Furthermore, in situ experiments comparing samples with and without nanocomposite formation provided crucial insights into the decomposition dynamics. In situ tracking allows to decipher the initial topochemical transformation of the layered precursor into a metal oxide phase, with the carbon content determining the extent of reduction. These findings provide fundamental understanding for the rational design of advanced energy materials of special industrial interest.